Educational stress: how are Ukrainian students dealing with it challenges - DUBCZAK, Halyna; SERDYUK, Lyudmila; TRAVERSE, Tetyana (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2025)
Background. This study was intended to draw the attention of researchers and specialists to the need for a comprehensive consideration of the problem of stress in educational activities. The purpose of the study was to examine the level of stress among modern Ukrainian students and to determine whether it has changed over the last ten years. The research focuses on identifying the most common causes of academic stress. The study considers the manifestations of stress in modern students. It analyzes the ways in which students cope with stressful situations in their daily lives. Differences in the features of educational stress between male and female students, as well as between students of higher education institutions and vocational schools, are identified.Methods. The study uses the technique of educational stress, which is a self-descriptive scale that allows you to identify: the main causes of academic stress; the level of academic stress; manifestations of stress in academic activities; methods for relieving stress; the level and main signs of exam stress. The analysis was performed on a group of 600 students (including 316 university students, 284 students of vocational schools; 283 men and 317 women) aged 15-45 years.Results. It is found out that for the majority of Ukrainian students, the main stressful situations are related to learning activities; the least stressful are group conflicts and cohabitation problems with other students. The level of examination stress of today's students is significantly higher than decades ago; it is significantly higher for university students than for students in vocational schools; for female students, it is higher than for male students. The most common manifestations of learning stress are behavioural; the least pronounced are physiological. It has been found that gender and the choice of stress relief are related.Conclusions. The conclusions are made about the need for organization of specifically targeted psychological work with students having high manifestations of educational and examination stress.
Keywords: students; educational stress; exam stress; stress factors; stress states